Metabolic Functions of G Protein-Coupled Receptors and β-Arrestin-Mediated Signaling Pathways in the Pathophysiology of Type 2 Diabetes and Obesity - Oliveira de Souza, Camila; Sun, Xuenan; Oh, Dayoung (Frontiers in Endocrinology, 2021)
Seven transmembrane receptors (7TMRs), often termed G protein-coupled receptors (GPCRs), are the most common target of therapeutic drugs used today. Many studies suggest that distinct members of the GPCR superfamily represent potential targets for the treatment of various metabolic disorders including obesity and type 2 diabetes (T2D). GPCRs typically activate different classes of heterotrimeric G proteins, which can be subgrouped into four major functional types: Gαs, Gαi, Gαq/11, and G12/13, in response to agonist binding. Accumulating evidence suggests that GPCRs can also initiate β-arrestin-dependent, G protein-independent signaling. Thus, the physiological outcome of activating a certain GPCR in a particular tissue may also be modulated by β-arrestin-dependent, but G protein-independent signaling pathways. In this review, we will focus on the role of G protein- and β-arrestin-dependent signaling pathways in the development of obesity and T2D-related metabolic disorders.